Pengaruh Hybrid Marketing Terhadap Customer Engagement Umkm Fashion di Kota Tangerang - Asmal Fajri; Nunu Maria; Suro Irwanto; Aska Dwi Rahmadhayanti; Ria Aulia (CV. ITTC INDONESIA, 2026)
This study examines the influence of hybrid marketing on customer engagement of fashion SMEs (Small and Medium Enterprises) in Tangerang City. Hybrid marketing, as an operational approach that integrates traditional and digital marketing, is grounded in the grand theory of Integrated Marketing Communication (IMC). This study employs a quantitative approach with explanatory research design. Data were collected from 120 active fashion SME owners in Tangerang City using purposive sampling and analyzed through multiple linear regression. The results indicate that: (1) traditional marketing (β = 0.248; p = 0.003) has a positive and significant effect on customer engagement; (2) digital marketing (β = 0.431; p = 0.000) is the strongest determinant of customer engagement; and (3) hybrid marketing simultaneously explains 62.1% of the variance in customer engagement (F = 95.714; p = 0.000). These findings confirm the relevance of IMC as a theoretical framework explaining the effectiveness of hybrid marketing in enhancing customer engagement for fashion SMEs.